Simplify the following expression (4x+5y) ^2-((4x-5y)^2
Answers
Answered by
2
Answer:
(4x+5y)-(4x-5y)
= (4x)+(5y)
+4(4x)(5y)-[(4x)
+(5y)
-2(4x)(5y)]
= 16x+25y
+40xy-[16x
+25y
-40xy]
= 16x+25y
+40xy-16x
-25y
+40xy
= 40xy+40xy
= 80xy
Answered by
0
Answer:
(
4
x
−
5
y
)
(
4
x
−
5
y
)
Expand
(
4
x
−
5
y
)
(
4
x
−
5
y
)
using the FOIL Method.
Tap for more steps...
4
x
(
4
x
)
+
4
x
(
−
5
y
)
−
5
y
(
4
x
)
−
5
y
(
−
5
y
)
Simplify and combine like terms.
Tap for more steps...
16
x
2
−
40
x
y
+
25
y
2
Similar questions